Investigations on strain rate dependent forming limits of 5xxx aluminium alloys for flow-line-free sheet metal forming - Klitschke Silke; Hauser Lukas; Liewald Mathias (MATEC Web of Conferences)
5xxx-AlMg(Mn) sheet metal alloys reveal a tendency to form flow lines during their forming process, known as the Portevin-Le Chatêlier effect (PLC effect). This phenomenon currently prevents these alloys from being used for the production of design-defining outer skin components in automotive body construction, despite their stable material states and excellent formability at room temperature (RT) without additional heat treatment. However, the occurrence of the PLC effect can be suppressed by increasing the forming speed, which is consistent with prevailing trends in sheet metal forming technology of modern press shops. In the present work, process windows for flow-line-free forming of 5xxx aluminium alloys were determined as a function of strain rate, facilitating their future use as outer skin automotive components. The deformation behaviour of the two alloys EN AW-5182 and EN AW-5754 was investigated under uniaxial and multiaxial loading within a strain rate range of 0.001 s−1 and 10 s−1. Obtained results have shown that, for strain rates between 1 s−1 to 4 s−1, or higher, both alloys can be deformed without flow lines on the specimen surface. Finally, new strain rate-dependent PLC characteristic curves were defined as PLC-free forming limits for the integration into usual FE forming simulations.